2016
DOI: 10.1186/s12957-016-0893-6
|View full text |Cite
|
Sign up to set email alerts
|

ALK-rearranged pulmonary adenocarcinoma in Thai Patients: From diagnosis to treatment efficacy

Abstract: BackgroundAnaplastic lymphoma kinase (ALK) gene rearrangement is detected in 3 % to 13 % of non-small cell lung carcinoma patients, and these patients benefit from ALK inhibitors. The aim of this study was to determine the prevalence, the clinical and histological characteristics and the treatment outcomes of ALK-rearranged lung adenocarcinoma using immunohistochemistry (IHC) IHC, reverse transcription polymerase chain reaction (RT-PCR) and fluorescence in situ hybridization (FISH) methodologies.MethodsA total… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…In this Comprehensive histological analysis in cases with ALK mutation confirmed that these tumours show histologic features distinct from the wild type cancers. Most of these tumours harbour a mixed morphological pattern (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…In this Comprehensive histological analysis in cases with ALK mutation confirmed that these tumours show histologic features distinct from the wild type cancers. Most of these tumours harbour a mixed morphological pattern (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…This fusion is created by an inversion of the short arm of chromosome 2 that binds exons 1-13 of EML4 (encoding echinoderm microtubule associated protein like 4) to exons 20-29 of ALK, resulting in the synthesis of a chimerical protein with constitutive ALK activity (86)(87)(88). Patients with ALK-rearranged ADC are usually young, never-smokers and women, showing moderately or poorly differentiated peripheral tumors (89,90). In general, ALK alterations are mutually exclusive with KRAS-EGFR mutations, having prognosis implications due to the impact of guidedtherapies (91).…”
Section: Alk Translocationsmentioning
confidence: 99%
“…Furthermore, with high sensitivity and specificity and rapid turnaround time and ease of analysis, qRT-PCR can detect as few as 1% of ALK-driven NSCLC cells [ 27 ]. Previous studies have shown that qRT-PCR is an effective method for detecting ALK rearrangement using cytology samples from patients with primary lung cancer [ 16 , 28 30 ]. The concordance level between different methods ranges from 99 to 100% in these studies.…”
Section: Discussionmentioning
confidence: 99%